Use of outdoor games in physical rehabilitation of children with a cerebral paralysis. - Vindiuk P.A; Volkova S.S (Kharkov National Pedagogical University, 2011)
We considered the estimation of energy in children's organism with cerebral paralysis. 16 children of secondary school age took part in research with spastic forms of a cerebral paralysis. It is established that children with a cerebral paralysis have the reduced energy parameters of the organism in comparison with children of the basic group of health. It is proved that specially organized outdoor games at the studies contribute to the growth of these indicators.